Pengaruh Terapi Musik Klasik Terhadap Lansia Penderita Insomnia - Napitupulu, Mastiur; ., Sutriningsih (Universitas Aufa Royhan, 2019)
Disorders of sleep patterns that often occur in the elderly are difficult to maintain sleep and if you wake up at night it is difficult to sleep again. Music therapy is a hearing stimulus that organizes melody, rhythm, harmony, color (timbre), shape, and style. The research objective was to determine the effect of classical music therapy on elderly people with insomnia. Types of quantitative research. The research design is quasy experiment. The one group pretest - post test design study design. The results of the study respondents aged> 65 years 30 people (100%), the majority were male 16 people (53.3%). The average score of insomnia before being given classical music therapy is 12.80 (insomnia), SD = 1808, minimum score of 11 and maximum score 19. With 95% CI, the average score of insomnia before being given classical music therapy is believed to be between 12.12-13.48. While the average score of insomnia after being given classical music therapy was 7.40 (no insomnia), SD = 2.31, a minimum score of 4 and a maximum score of 13. With 95% CI, the average score of insomnia before classical music therapy was believed to be between 6.74- 8.46. The results of the shapiro wilk test analysis of the average score of insomnia before intervention p = 0.000 (p <0.05) means that the data are not normally distributed and the score of insomnia after intervention p = 0.156 (p> 0.05) means that data is normally distributed. The paired Wilcoxon test p = 0.000 (p <0.05). It was concluded that there were changes in respondents before being given an intervention experiencing insomnia and after getting the intervention they did not experience insomnia.